2002
DOI: 10.1207/s1532799xssr0604_04
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Diversity and the Development of Reading Skills: A Longitudinal Study

Abstract: The purpose of this study was to examine whether the same component processes are involved in reading acquisition for children with varying levels of proficiency in English in kindergarten and the first grade. The performance of 858 children was examined on tasks assessing basic literacy skills, phonological processing, verbal memory, and syntactic awareness. There were 727 children who were native English speakers (NS children) and 131 children who spoke English as a second language (ESL children). Although E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
138
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(160 citation statements)
references
References 53 publications
19
138
3
Order By: Relevance
“…However, there are also studies that showed that the degree of syntactic awareness in L1 was not transferred to L2 (Chiappe, Siegel & Wade-Woolley, 2002). Furthermore, several studies have shown that language components of L1, such as phonological, morphological and syntactic knowledge, spelling knowledge and vocabulary contribute to the understanding of L2 (Abu-Rabia & Bluestein-Danon, 2012;Abu-Rabia & Shakkour, 2014;Abu-Rabia et al, 2013;Kahn-Horwitz et al, 2005;Kieffer & Lesaux, 2008;Zhang & Koda, 2008).…”
Section: Research Findings On the Linguistic Skills Transfer Between mentioning
confidence: 99%
“…However, there are also studies that showed that the degree of syntactic awareness in L1 was not transferred to L2 (Chiappe, Siegel & Wade-Woolley, 2002). Furthermore, several studies have shown that language components of L1, such as phonological, morphological and syntactic knowledge, spelling knowledge and vocabulary contribute to the understanding of L2 (Abu-Rabia & Bluestein-Danon, 2012;Abu-Rabia & Shakkour, 2014;Abu-Rabia et al, 2013;Kahn-Horwitz et al, 2005;Kieffer & Lesaux, 2008;Zhang & Koda, 2008).…”
Section: Research Findings On the Linguistic Skills Transfer Between mentioning
confidence: 99%
“…Recurring negotiations of meaning characterized reading and writing sessions (Damber, 2009;Droop & Verhoeven, 2003). The large amount of reading brought about learning of less frequent words occurring in print, thus extending the pupils' vocabularies (Chiappe, Siegel, & Wade-Wooley, 2002). Process writing, vocabulary, and critical awareness exemplify domains where dialogues are critical to further development, irrespective of the children's language background.…”
Section: Comparative Discussion Of the Two Practicesmentioning
confidence: 99%
“…Taken together, syntactic awareness refers to the ability to reflect upon and dominate the inner grammatical structure of a sentence and syntactic rules (Chiappe, Siegel, & Wade-Woolley, 2002). Syntactic awareness can help children organize the decoded words into meaningful sentences, and reflect on the errors in the sentences, therefore, syntactic awareness essentially represents children's attentional control ability.…”
Section: Syntactic Awarenessmentioning
confidence: 99%